Regulation of Brucella virulence by the two-component system BvrR/BvrS - López-Goñi, Ignacio (2002)
The Brucella BvrR/BvrS two-component regulatory system is highly similar to the regulatory and sensory proteins of Sinorhizobium and Agrobacterium necessary for endosymbiosis and pathogenicity in plants, and very similar to a putative system present in the animal pathogen Bartonella. Mutations in the bvrR or bvrS genes hamper the penetration of B. abortus in non-phagocytic cells and impairs intracellular trafficking and virulence. In contrast to virulent Brucella, BvrR/BvrS mutants do not recruit small GTPases of the Rho subfamily required for actin polymerization and penetration to cells. Dysfunction of the BvrR/BvrS system alters the outer membrane permeability, the expression of several group 3 outer membrane proteins and the pattern of lipid A acylation. Constructs of virulent B. abortus chimeras containing heterologous LPS from the bvrS− mutant demonstrated an altered permeability to cationic peptides similar to that of the BvrR/BvrS mutants. We hypothesize that the Brucella BvrR/BvrS is a system devoted to the homeostasis of the outer membrane and, therefore in the interface for cell invasion and mounting the required structures for intracellular parasitism.